The role of social dialogue in the transfer of the dual system of vocational education and training: The case of Serbia - Margarita Langthaler; Proloeng Top (Austrian Foundation for Development Research (ÖFSE), 2023)
The international transfer of dual systems of vocational education and training (VET) has grown on a global scale. This is due to low youth unemployment rates and high economic productivity in German-speaking countries, where the dual systems are historically rooted. At the governance level, an institutionalised tripartite dialogue between government, employer representatives and organised labour underpins dual VET in German-speaking countries. In the transfer processes, there is an observable trend towards reducing this tripartite institutional setting to a dialogue between employers and the government. However, neglecting the role of employees and their interest groups might jeopardise expected human development effects of dual system transfer such as decent work, improved standards of living and social cohesion. This paper will analyse the policy transfer process to Serbia where a dual VET track was introduced in 2017. To visualise political interests rather than VET improvement as main drivers of the VET reform, the paper will deploy a political economy and institutionalist lens. It argues that tripartite social dialogue is an important element of dual VET transfer if the latter is supposed to contribute to human development.
Keywords: 330; dual vocational education and training; education policy transfer; social dialogue; human development